Banker Plant Efficacy to Boost Natural Predators for Management of Field Populations of Scirtothrips dorsalis Hood (Thysanoptera Thripidae) in Strawberries - Allan Busuulwa; Alexandra M. Revynthi; Oscar E. Liburd; Sriyanka Lahiri (Insects)
Since 2015, Scirtothrips dorsalis Hood has emerged as the main pest of strawberries in Florida. Given the limited management options, there is a recognized need to expand on the management strategies for this pest. Therefore, we explored the possibility of using banker plants to recruit naturally occurring predators of thrips into strawberry fields to suppress S. dorsalis. The study began in the 2021–2022 strawberry season where five banker plants were screened to determine which ones could consistently attract thrips predators by flowering throughout the strawberry season. Capsicum annum L. (ornamental pepper) and Lobularia maritima L. (sweet alyssum) were selected for further evaluation. In the 2022–2023 strawberry season, using a randomized complete block design we assessed the capability of these banker plants to attract thrips predators into the strawberry field. In addition, we examined how the banker plant distance from the strawberry plants influenced the S. dorsalis pest suppression. Our results showed that strawberries located within 3.7 m of ornamental pepper plants had less leaf damage from S. dorsalis compared with those farther away, which may result from the repellent effect of the ornamental peppers. Additionally, Geocoris spp. and Orius spp. were identified as the main thrips predators in the system, although in relatively low numbers. Therefore, these results highlight the potential of incorporating ornamental pepper as a banker plant in strawberry production. Additional applications of this research are explored below.